2011
DOI: 10.4049/jimmunol.1100610
|View full text |Cite
|
Sign up to set email alerts
|

Selenite Induces Posttranscriptional Blockade of HLA-E Expression and Sensitizes Tumor Cells to CD94/NKG2A-Positive NK Cells

Abstract: CD94/NKG2A is an inhibitory receptor that controls the activity of a large proportion of human NK cells following interactions with the nonclassical HLA class Ib molecule HLA-E expressed on target cells. In this study, we show that selenite (SeO32−), an inorganic selenium compound, induces an almost complete loss of cell surface expression of HLA-E on tumor cells of various origins. Selenite abrogated the HLA-E expression at a posttranscriptional level, since selenite exposure led to a dose-dependent decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 69 publications
2
41
0
Order By: Relevance
“…This fits with the idea that the level of surface HLA‐E is mainly regulated through the availability and binding of peptides . Moreover, our data are in‐line with a recent study in which HLA‐E expression was abrogated by selenite, resulting in a decrease in cellular HLA‐E protein expression, whereas RNA levels remained intact , confirming regulation of HLA‐E at the post‐transcriptional level. Interestingly, we observed that the induced level of HLA‐E with peptides was inhibited by CHX.…”
Section: Discussionsupporting
confidence: 90%
“…This fits with the idea that the level of surface HLA‐E is mainly regulated through the availability and binding of peptides . Moreover, our data are in‐line with a recent study in which HLA‐E expression was abrogated by selenite, resulting in a decrease in cellular HLA‐E protein expression, whereas RNA levels remained intact , confirming regulation of HLA‐E at the post‐transcriptional level. Interestingly, we observed that the induced level of HLA‐E with peptides was inhibited by CHX.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the inorganic selenite could both promote cellular apoptosis and block HLA‐E expression in cancer cells of various origins 13. The decrease in the expression level of HLA‐E further renders cancer cells susceptible to NK cells by oxidative stress 14. Seleninic acid (RSeO(OH)) is the oxidation products of diselenide with the same chemical valence of Se as selenite (SeO 3 2− ).…”
Section: Figurementioning
confidence: 99%
“…The mechanism of action of selenium is not entirely known, but it induces apoptosis of tumor cells by generating an oxidative stress, which may be more effective on tumor cells compared to healthy cells (118, 119). Alternatively, selenium blocks the synthesis of HLA-E and consequently increases cytotoxicity mediated by NKG2A-positive NK cells (120). This effect, combined to the direct toxicity on tumor cells may result in reduced disease progression and improved survival.…”
Section: Targeting Inhibitory Receptorsmentioning
confidence: 99%